3D printed mixed flow reactor for geochemical rate measurements. (February 2018) - Michel, F. Marc; Rimstidt, J. Donald; Kletetschka, Karel
Abstract: Desktop 3D printing is a rapid, low-cost, and flexible method for fabricating chemical reactors for low temperature geochemical investigations and engineering tests. Reactor designs can be easily shared between research groups. Here we demonstrate how a mixed flow reactor (MFR) designed to measure mineral precipitation rates is fabricated by desktop additive manufacturing (3D printing). Models of the MFR top and base were created by computer-aided design software and used to generate stereolithography input files. These files were converted to physical models using stereolithography (SLA) 3D printing technology. Comparison of the model input files to actual prototypes showed that the manufactured reactor parts matched the model as closely as machined parts match mechanical drawings. Although this reactor was designed to measure mineral precipitation rates, it can be easily modified for use in mineral dissolution experiments. The reactor can also be used to synthesize large quantities of solids from a solution with a fixed composition and be combined with in situ scattering and spectroscopic methods for real time studies of mineral growth/dissolution processes. Highlights: A method for designing and fabricating mixed flow reactors is proposed. The method uses desktop stereolithography 3D printing technology. Fabrication is rapid and low-cost compared with conventional machining. The digital models are adaptable and easily shared between research groups. Reactors can be customized for different types of geochemical studies.